As Time Goes by: A rTMS Study on Age-Related Changes in Sentence Comprehension - Berlingeri, Manuela; Carioti, Desiré; Danelli, Laura; Lo Gerfo, Emanuele (Frontiers in Aging Neuroscience, 2018)
It is well established that off-line sentence judgment tasks (oSJTs) typically rely on phonological working memory (WM), beyond specific linguistic processing. Nevertheless, empirical findings suggest that a juvenile level of performance in an oSJT could be associated with the recruitment of age-specific additional supportive neural network in healthy aging. In particular, in one of our previous study, healthy elderlies showed the additional activation of associative visual cortices when compared with young controls. We suggested that age-related hyperactivations, during an auditory sentence judgment task, might represent the neurofunctional correlate of the recruitment of compensatory strategies that are necessary to maintain a juvenile level of performance. To explicitly test this hypothesis we adopted repetitive transcranial magnetic stimulation (rTMS). Twelve healthy elderlies and 12 young participants were engaged in an off-line semantic plausibility judgment task while rTMS was delivered over: (1) the left inferior frontal gyrus (LIFG; i.e., a core region of the WM network); (2) the precuneus; and (3) a Control Site (vertex). Results showed a significant main effect of Stimulation Site and a significant Group-by-Stimulation Site interaction effect. In particular, the rTMS stimulation of the LIFG slowed down reaction times (RTs) both in young and healthy elderly participants, while only healthy elderlies showed an increment of RTs during the stimulation of the precuneus. Taken together our results further support the idea that the maintenance of a juvenile level of performance in graceful aging may be associated with task-specific compensatory processes that would manifest them-selves, from the neurofunctional point of view, by the recruitment of additional neural supportive regions.